Understanding a new generation incubation model: The accelerator. (April 2016) - Pauwels, Charlotte; Clarysse, Bart; Wright, Mike; Van Hove, Jonas
Abstract: Prior research hints at the accelerator as a new generation incubation model. Accelerators have become an umbrella term for any program providing a service structure of mentorship, networking opportunities and access to funding. The challenge, however, is to understand their distinctive characteristics and profiles geared towards reinforcing business start-ups. How do accelerators operate as a new generation incubation model and how do they differ from existing incubation mechanisms? This inductive study investigates 13 accelerators across Europe and adopts a design lens to identify the accelerator model's key design parameters. We identify five key building blocks and distinguish between three different types of accelerators, taking the primary design theme of the accelerator into account. We contribute to the incubation literature by extending recognition of the heterogeneity of incubation models, by delineating the accelerator as a distinctive incubation model and by introducing the design lens as a useful theoretical framework to investigate incubation models and their evolution. Highlights: We adopt a design lens to investigate incubation models and their evolution. Accelerators constitute a new generation incubation model. We identify the key design parameters of accelerators. We identify three different types of accelerators. We clarify heterogeneity within the accelerator model.